2016
DOI: 10.1002/jmv.24610
|View full text |Cite
|
Sign up to set email alerts
|

Increased replication capacity following evolution of PYxE insertion in Gag‐p6 is associated with enhanced virulence in HIV‐1 subtype C from East Africa

Abstract: This is the first evidence of polymerase independent increased virulence and RC in HIV-1C following PYxE-insertion that is associated with suboptimal CD4 T-cell gain following therapy initiation. J. Med. Virol. 89:106-111, 2017. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
(27 reference statements)
6
12
0
Order By: Relevance
“…This correlation suggests that HIV-1C strains with a PYxE insertion have a growth advantage compared to wild type HIV-1C. This is also in line with our earlier study that HIV-1C PYQEi viruses are more replication competent as well as more pathogenic (17).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…This correlation suggests that HIV-1C strains with a PYxE insertion have a growth advantage compared to wild type HIV-1C. This is also in line with our earlier study that HIV-1C PYQEi viruses are more replication competent as well as more pathogenic (17).…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, the insertion appears more frequent among patients on antiretroviral therapy, e.g., ritonavir-boosted protease inhibitors (PI), compared to therapy naïve patients in India, and more frequent in therapy-failure patients in South Africa (15, 16). Moreover, lower pre-therapy CD4 + T cell counts, higher plasma viral loads, and reduced increase in CD4 + T cell counts were noted to be associated with PYxE insertion in HIV-1C patients compared to patients with wild type HIV-1C from East Africa (17). Furthermore, we observed that increased replication fitness in PYQE inserted HIV-1C viruses was polymerase independent (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also of interest that an unusual mutant with deletion at residues 482 and 483, shown to disrupt Alix binding (68), was previously associated with nonprogressive HIV-1 infection (69), indicating that the ability to bind Alix may influence disease progression. Furthermore, it was recently described that a PYxE insertion (at the same position as the LY motif) in some East African subtype C isolates enhanced the replication capacity and virulence of these isolates compared to subtype C isolates without the insertion (70).…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been hypothesized that HIV-1 subtype C isolates, which comprise more than >50% of infections worldwide (Hemelaar, 2012), may be inherently more transmissible - possibly because of subtype-specific motifs within Env-gp120 that modulate interactions with host cell entry receptors (Walter et al, 2009) - though this remains controversial (Kahle et al, 2014). Subtype-specific differences in HIV-1 entry efficiency (Marozsan et al, 2005), replication capacity (Aralaguppe et al, 2016; Konings et al, 2006), and the function of viral accessory proteins Vif (Binka et al, 2012; Iwabu et al, 2010) and Nef (Mann et al, 2013) have also been described. Methods to assess the function of other HIV-1 proteins encoded by natural sequences are thus warranted.…”
Section: Introductionmentioning
confidence: 99%